Fiber Networks: The Plasticity of Nanofibrous Matrix Regulates Fibroblast Activation in Fibrosis (Adv. Healthcare Mater. 8/2021). Issue 8 (21st April 2021) - Jia, Yuanbo; Wang, Yanzhong; Niu, Lele; Zhang, Hang; Tian, Jin; Gao, Dengfeng; Zhang, Xiaohui; Lu, Tian Jian; Qian, Jin; Huang, Guoyou; Xu, Feng
Abstract : Little attention has been paid to the effect of matrix fiber‐network plasticity at the microscale. In article number 2001856, Jin Qian, Guoyou Huang, Feng Xu, and co‐workers find a significant decrease in plasticity of native fibrotic tissues, which is associated with increased matrix crosslinking. They demonstrate that the decrease of matrix plasticity promotes fibroblast activation and spreading using a plasticity‐controlled 3D culture system, which is mediated through cytoskeletal tension and nuclear translocation of Yes‐associated protein.